Nanorobots mediated drug delivery for brain cancer active targeting and controllable therapeutics - Mengze Xu; Zhaoquan Qin; Zhichao Chen; Shichao Wang; Liang Peng; Xiaoli Li; Zhen Yuan (Discover Nano)
Abstract Brain cancer pose significant life-threats by destructively invading normal brain tissues, causing dysneuria, disability and death, and its therapeutics is limited by underdosage and toxicity lying in conventional drug delivery that relied on passive delivery. The application of nanorobots-based drug delivery systems is an emerging field that holds great potential for brain cancer active targeting and controllable treatment. The ability of nanorobots to encapsulate, transport, and supply therapies directly to the lesion site through blood–brain barriers makes it possible to deliver drugs to hard-to-reach areas. In order to improve the efficiency of drug delivery and problems such as precision and sustained release, nanorobots are effectively realized by converting other forms of energy into propulsion and motion, which are considered as high-efficiency methods for drug delivery. In this article, we described recent advances in the treatment of brain cancer with nanorobots mainly from three aspects: firstly, the development history and characteristics of nanorobots are reviewed; secondly, recent research progress of nanorobots in brain cancer is comprehensively investigated, like the driving mode and mechanism of nanorobots are described; thirdly, the potential translation of nanorobotics for brain diseases is discussed and the challenges and opportunities for future research are outlined.